FAKTOR-FAKTOR YANG MEMPENGARUHI DIVIDEND POLICY PERUSAHAAN GO PUBLIC DI INDONESIA - Nik Amah (Universitas PGRI Madiun, 2012)
This research tests the effect of profitability, liquidity, investment opportunity, risk, and firm’s size on dividend policy of go public company in Indonesian over the period 2006-2008. Population of this research is all of public companies that listed at Indonesian Stock Exchange. Sampling method uses purposive sampling method. Hypothesis test uses multiple regression analysis. The results of this research show that: profitability, liquidity, investment opportunity, risk, and firm’s size simultaneously affect on dividend policy; and each of independent variables partially affects on dividend policy.